The expression 4x - 3y - 5x - 2y can be simplified by combining like terms. Like terms have the same variables raised to the same powers. In this case, the x terms are like terms and the y terms are like terms. Combining the x terms, we get -x, and combining the y terms, we get -5y. Therefore, the simplified expression is -x - 5y.
5x + (3y-x) + (10-2y) = 5x + 3y - x + 10 -2y = 5x - x + 3y - 2y + 10 = 4x + y +10
4x-2y
5x -6y=-30 5x-6y=30 (2x+3y) (2x-3y)=30 4x+6y=30 4x=30 x=30/4
The solution of 4x plus 3y -9 and x -3 is; 5x+3y-3.
5x-2y+3z-2x-y-4z=3x-3y-z
5x + (3y-x) + (10-2y) = 5x + 3y - x + 10 -2y = 5x - x + 3y - 2y + 10 = 4x + y +10
If you mean: 5x+2y+x-3y then it is 6x-1y
(3x+2y)*(5x-3y) =3x*5x + 3x*(-3y) + 2y*5x + 2y*(-3y) [This is sometimes called the FOIL method - You multiply the First members of each bracket, then the Outers, Inners, Lasts] = 15x2 - 9xy + 10xy - 6y2 = 15x2 + xy - 6y2
3y2 - 2y + 6xy - 4x = y(3y - 2) + 2x(3y - 2) = (y + 2x)*(3y - 2)
5x+3y
4x+3y-2x+y 4x-2x+3y+y 2x+4y Taking out 2 common 2(x+2y) Hence the required answer is 2(x+2y)
5x - 3y -7x + 2y +3x = (5-7+3)x + (-3+2)y = x - y
4x-2y
4x + 3y = 8x + y so 3y - y = 8x - 4x ie 2y = 4x so y = 2x
It is: 6x-5y simplified
5x -6y=-30 5x-6y=30 (2x+3y) (2x-3y)=30 4x+6y=30 4x=30 x=30/4
The solution of 4x plus 3y -9 and x -3 is; 5x+3y-3.